MECHANICAL DAMAGE TO COTTON FIBER DURING PRIMARY PROCESSING OF RAW COTTON - Mirkhojaev Mirjamol Mirkarimovich; Tadjibayev Anvar Avazovich (Web of Journals Publishing, 2025)
The article presents analyses of mechanical damage to cotton fiber and its impact on quality during technological transitions at a cotton ginning plant.
Keywords: Cluster, cotton, raw materials, fiber, pile, UXK line, raining, pressing, standard O'zMSt, HVI, length, strength.